THE INFLUENCE OF SOCIAL MEDIA BRANDING ON CUSTOMER ENGAGEMENT FOR JAKARTA SUSTAINABLE TRANSPORT - Yulianne Safitri; Lidya Wati Evelina; Naufal Egha Syahputra (Bina Nusantara University, 2020)
The researchaimedto understand the relationship and influence of Instagram @mrtjkt social media branding on customer engagement as an effort to increase the use of MRT as sustainable green transportation to reduce traffic congestion and pollution in Jakarta. The quantitative research approach with a survey method was carried out to 100 respondents from the total population on Instagram Followers @mrtjkt. The quantitative analysis was implemented using correlation test, coefficient determination test, and simple regression analysis. The data validity techniqueswerethe validity test, reliability test and normality test. Research resultshows thatH0isrejected and H1is acceptedsince it shows relationships and influences between Instagram social media branding on MRT Jakarta customer engagement.